An evaluation of final disposal alternatives for municipal solid waste through life cycle assessment: A case of study in Colombia. Issue 1 (1st January 2021) - Caicedo-Concha, Diana M; Sandoval-Cobo, John J; Stringfellow, Anne; Colmenares-Quintero, Ramon Fernando
Abstract: Landfilling is still the most common technology used in developing countries for the final disposal of municipal solid waste (MSW), albeit the negative impacts on the environment such as those caused by the release of greenhouse gases (GHG) that contribute to global warming (GW). The Colombian government set a target of 20% reduction in GHG emissions by year 2030, for which the solid waste management sector has an important role to play. Also, the achievement of the targets of sustainable development goals (SDG) is playing a key role for the government agenda and will do so for the next years. In this context, there is an important room for improvement of the management alternatives in currently operative landfills in the country, especially in terms of measures to reduce fugitive air emissions and leachates. This paper evaluates, using life cycle assessment (LCA) methods, the environmental impacts associated with a landfill in Colombia under four different scenarios: open dumps (zero) and conventional landfill under three landfill gas (LFG) management alternatives: venting (a), flaring (b), and energy recovery (c). The impact categories as well as the life cycle impact assessment (LCIA) methods used were determined through the review of LCA studies for MSW management systems in developing countries. Main results show that global warming potential (GWP) was the main environmental impact caused by the landfill operation under the conditions considered; however, GWP was significantly reduced with the shifting from management scenarios with no LFG treatment (o and a: common to most landfills in developing countries) to scenarios where LFG is either flare (b) or utilized for energy production (c). These results suggest that adoption of technologies for LFG capture, burn, and energy recovery must be considered if important reductions of GHGs are expected from the waste management sector, as well as to provide economic incentives to improve the operational sustainability of landfills in developing countries.